The Impact of Nutrition, Physical Activity, and Stress on Cardiovascular Diseases in Youth - Jasmina, Avazova; Abdumo`minovna, Arsenova Muhabbat (American Journal of Biomedicine and Pharmacy, 2025)
This scientific article is dedicated to examining the interplay of factors such as nutrition, physical activity, and stress in the development of cardiovascular diseases (CVD) in the younger generation. The article explores the urgency of the problem of increasing CVD among young people, as well as the importance of prevention and early diagnosis in preventing these diseases. The negative impact of modern lifestyles, unhealthy eating habits, physical inactivity, and chronic stress on the health of young people and their role in the development of CVD is discussed. Furthermore, the article considers how promoting a healthy lifestyle, specifically through balanced nutrition, regular physical activity, and stress management, can affect the manifestation of CVD in young people and how important changes during youth are in their prevention.